Tinjauan Hukum Islam terhadap Praktik Akad Nikah Bagi Mempelai Tunarungu di KUA Kecamatan Badas Kabupaten Kediri - Ahmad Hafid Safrudin; Sholikhan (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2020)
The marriage contract is an agreement made by the two brides who are married in the form of a qabul consent. Consent is the submission of the first party, while qabul is acceptance from the second party. In this study, the object of study is the bride and groom, one of whom is deaf. Deaf are people who can't hear like normal people in general. So that in reciting the marriage contract cannot be clear. While in the provisions of Islamic law, the pronunciation of the marriage contract must be clear. This is a reference for Islamic law in answering complex problems in society. And such marriages have been carried out in KUA Badas district. From this research, the author intends to dig up the legal basis for deaf marriages who cannot hear because they are congenital or because of a disease. In the case of qabul (acceptance), the marriage contract can be done according to the bride's abilities. This can be done in two ways, namely by using sign language, and the sign language can be understood by witnesses, secondly, it can be done by using writing